Analisis Pengaruh Spread Tingkat Suku Bunga, Rasio Keuangan Bank (CAR, NPL, LDR), dan BI Rate terhadap Penyaluran Kredit Umkm pada Bank Umum Go Public di Indonesia - Muhammad Ilham Ashari; Anandhiya Intan Prabandari; Viviana Mayasari (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
This study aims to analyse the effect of the Interest Rate Spread (NIM), CAR, NPL, LDR, and BI Rate on MSME lending by publicly listed commercial banks in Indonesia during the period 2010–2015, using the panel data regression method with a Fixed Effect Model (FEM) approach. The results indicate that NIM has a positive but insignificant effect, CAR and LDR have positive and significant effects, NPL has a negative and significant effect, while the BI Rate has a negative and insignificant effect on MSME lending. The findings imply the importance of the role of the government, Bank Indonesia, and the Financial Services Authority (OJK) in strengthening MSME support and maintaining the stability and supervision of banking financial ratios to enhance MSME credit distribution optimally.